Diels-alder reaction of tropones with arynes: synthesis of functionalized benzobicyclo[3.2.2]nonatrienones - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; Bisht, Rajesh H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2014)
A new procedure for the mild, practical, and scalable Diels–Alder reaction of tropones with arynes is reported. Differently substituted tropones undergo selective [4 + 2] cycloaddition with arynes generated in situ by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates, allowing the formation of functionalized benzobicyclo[3.2.2]nonatrienone derivatives in moderate to good yields. In addition, the photophysical properties of the cycloadducts are presented.